Analysis of Sugarcane Agroindustry Income: Case Study on Sugarcane Brown Sugar Agroindustry in Sungai Asam Village, Kayu Aro District, Kerinci Regency - Oliviandari, Windi; Yanita, Mirawati; Effran, Endy (JALOW | Journal of Agribusiness and Local Wisdom, 2024)
This study aims to: (1) Describe an overview of the sugar cane brown sugar processing agro-industry in Sungai Asam Village, Kayu Aro Barat Subdistrict, Kerinci Regency. (2) Analyze the income and acceptance of sugar cane brown sugar agro-industry in Sungai Asam Village, Kayu Aro Barat Subdistrict, Kerinci Regency. Data collection in this thesis was conducted using observation and interview methods. Interviews were conducted with 7 agro-industries located in Sungai Asam Village, West Kayu Aro Subdistrict, Kerinci Regency. The analysis method used is descriptive analysis analysis, income analysis. Based on the results of the study, there are 16 agro-industries that developed in Sungai Asam Village, West Kayu Aro Subdistrict, Kerinci Regency, spread across four hamlets. One of the hamlets that has the most agroindustry is Block C Hamlet with a total of 7 agroindustries (1) The Sugar Cane Agroindustry in Sungai Asam Village is still categorized as a small-scale industry which is founded on the background because the majority of the people of Sungai Asam Village plant sugar cane plants. (2) The average income received by the cane brown sugar agroindustry is greater than the UMP value of Kerinci Regency. From the results of these calculations, the average R / C Ratio value of agro-industry is 2.22, so agro-industry in Sungai Asam Village, Kayu Aro District, Kerinci Regency is feasible or profitable to continue.